Art of the ancestors : spatial and temporal patterning in the ceiling rock art of Nawarla Gabarnmang, Arnhem Land, Australia - Gunn, Robert G., (Archaeopress archaeology., 2018)
Focusing on the ceiling art at Nawarla Gabarnmang, one of the richest rock art sites in Arnhem Land (in Australia's Northern Territory), this work presents a new systematic approach to the archaeological recording and documentation of rock art developed to analyse the spatial and temporal structure of complex rock art panels.